ChemInform Abstract: Pd‐Catalyzed Cascade Cyclization by Intramolecular Heck Insertion of an Allene—Allylic Amination Sequence: Application to the Synthesis of 3, 4‐Fused Tricyclic Indoles. Issue 41 (October 2015) - Nakano, Shun‐ichi; Inoue, Naoya; Hamada, Yasumasa; Nemoto, Tetsuhiro
Abstract A novel protocol for the cascade cyclization of allenes derivatives to form three types of 3, 4‐fused tricyclic indoles is reported.